Superior colliculus modulates cortical coding of somatosensory information - Saba Gharaei (Nature Portfolio, 2020)
While there is no direct pathway from the superior colliculus to the cortex, the authors find that the superior colliculus modulates sensory-evoked responses in the somatosensory cortex. This modulation by the superior colliculus is mediated via a powerful di-synaptic pathway through the thalamus.